1996
DOI: 10.1002/j.1460-2075.1996.tb01033.x
|View full text |Cite
|
Sign up to set email alerts
|

Targeted mutagenesis of acyl-lipid desaturases in Synechocystis: evidence for the important roles of polyunsaturated membrane lipids in growth, respiration and photosynthesis.

Abstract: Acyl‐lipid desaturases introduce double bonds (unsaturated bonds) at specifically defined positions in fatty acids that are esterified to the glycerol backbone of membrane glycerolipids. The desA, desB and desD genes of Synechocystis sp. PCC 6803 encode acyl‐lipid desaturases that introduce double bonds at the delta12, omega3 and delta6 positions of C18 fatty acids respectively. The mutation of each of these genes by insertion of an antibiotic resistance gene cartridge completely eliminated the corresponding d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
143
1
5

Year Published

1998
1998
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 223 publications
(155 citation statements)
references
References 43 publications
(34 reference statements)
6
143
1
5
Order By: Relevance
“…Lipids are mostly involved in the responses to temperature stresses by the altered level of unsaturation of their fatty acids (38), but the induction of the desaturase system responsible for the altered unsaturation is additionally light-regulated (39). Unsaturated lipids are further needed in the repair of the PSII reaction centers after photoinhibitory destruction (40).…”
Section: Discussionmentioning
confidence: 99%
“…Lipids are mostly involved in the responses to temperature stresses by the altered level of unsaturation of their fatty acids (38), but the induction of the desaturase system responsible for the altered unsaturation is additionally light-regulated (39). Unsaturated lipids are further needed in the repair of the PSII reaction centers after photoinhibitory destruction (40).…”
Section: Discussionmentioning
confidence: 99%
“…The appearance of a visible phenotype may also be prevented by residual 20:4. Deletions of several desaturases in Synechocystis became critical only if the ∆6-and ∆12-desaturase were knocked out together, whereas a reduction in trienoic acids without affecting dienoic acids was not critical (Tasaka et al, 1996).…”
Section: Functional Analysis Of Ppdes6 In P Patens and S Cerevisiaementioning
confidence: 99%
“…PCC 6803 in which the desA and desD genes for the ⌬12 and ⌬6 desaturases, respectively, had been inactivated by targeted mutagenesis (6). The desA Ϫ ͞desD Ϫ cells contain monounsaturated but not polyunsaturated fatty acids, whereas wild-type cells contain polyunsaturated fatty acids such as di-, tri-, and tetraunsaturated fatty acids (7).…”
mentioning
confidence: 99%
“…By comparing these two strains we found that polyunsaturated fatty acids are essential for growth in Synechocystis sp. PCC 6803 at low temperatures (6).…”
mentioning
confidence: 99%
See 1 more Smart Citation